2021
DOI: 10.1080/15205436.2020.1870144
|View full text |Cite
|
Sign up to set email alerts
|

Prospect Theory in Times of a Pandemic: The Effects of Gain versus Loss Framing on Risky Choices and Emotional Responses during the 2020 Coronavirus Outbreak – Evidence from the US and the Netherlands

Abstract: During the 2020 coronavirus pandemic, governments across the globe relied heavily on the legacy media, not only to inform citizens about fast-paced developments in the midst of a crisis, but also to stimulate compliance with strict interventions. Prospect theory postulates that gain versus loss framing may affect preferences for different interventions. In a conceptual replication of Tversky and Kahneman's seminal prospect theory, findings from surveys in the US and the Netherlands (N = 1,121) demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
2
39
0
11
Order By: Relevance
“…Cross-country variations in risk aversion and the framing effect further suggest that important macro-level predictors of choice under risk are yet to be uncovered, with potential practical implications for large-scale crisis management. Also on the practical side, our failure to find evidence for an association between the framing manipulation and the willingness to comply with safety guidelines-along with similar failures from other studies conducted during the coronavirus pandemic [79][80][81][82]-suggests that the framing manipulation is of limited use as a tool to promote compliant behavior. Distinguishing between what framing can and cannot achieve may be of importance to both researchers and authorities around the world searching for the optimal way of communicating their messages during a crisis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Cross-country variations in risk aversion and the framing effect further suggest that important macro-level predictors of choice under risk are yet to be uncovered, with potential practical implications for large-scale crisis management. Also on the practical side, our failure to find evidence for an association between the framing manipulation and the willingness to comply with safety guidelines-along with similar failures from other studies conducted during the coronavirus pandemic [79][80][81][82]-suggests that the framing manipulation is of limited use as a tool to promote compliant behavior. Distinguishing between what framing can and cannot achieve may be of importance to both researchers and authorities around the world searching for the optimal way of communicating their messages during a crisis.…”
Section: Discussionsupporting
confidence: 59%
“…Yet, studies that did explicitly use coronavirus-related scenarios in risky-choice framing tasks also failed to find evidence for carryover effects. For instance, while gain vs. loss framing did impact choosing the safe vs. risky preventive programs within the framing scenario, it was not associated with support for preventive measures to fight the coronavirus outside the scenario [79]. Another study [80] found a significant three-way interaction between frame, type of scenario (coronavirus vs. the original DP), and emotionality on compliant behavior, such that participants rating high on emotionality were more willing to comply with preventive guidelines when information was framed in terms of gains but only in the case of the coronavirus scenario.…”
Section: Risky-choice Framing and Compliancementioning
confidence: 93%
“…For example, Jordan et al (2020) conducted a study during the early phase of the COVID-19 pandemic (April 17-30, 2020) and found that when a health message was framed in a way that led to a perceived public threat from COVID-19, people were willing to engage in more preventative measures. Hameleers (2021) examined how framing a policy preference in terms of gains and losses on a hypothetical COVID-19 policy would affect decision-making. His results indicated that when the public-health message was framed as a loss (triggering loss aversion), more risk-seeking policy interventions were preferred by individual decision-makers.…”
Section: The Framing Effect and Risky Decision-makingmentioning
confidence: 99%
“…Although recent studies have examined the effects of message framing on decision-making during the COVID-19 pandemic, the results appear to vary based on the level of uncertainty in each society and in each phase of the pandemic (e.g., Hameleers, 2021;Jordan et al, 2020;Sanders et al, 2020). For example, people were not affected by loss framing when asked about their lockdown preference and their intention to adhere to public-health guidelines (e.g., they were not likely to be risk-seeking when presented with a loss-framed message) (Sanders et al, 2020).…”
Section: The Present Studymentioning
confidence: 99%
“…Although PT has been continually developing since its invention [17] and has been broadly analyzed in various sectors such as IT [18], transportation [19] services [20], health issues [21], and has been particularly influential in the fields of economics [22], psychology [23], sociology [24], etc., there is a little evidence on PT in the energy sector [25] or in the energy sustainability field (Figure 1). Some research (bibliometric analysis) has been done on the subject of "Sustainable Industry 4.0" [26] but it has not considered energy issues for assessing technologies.…”
Section: Introductionmentioning
confidence: 99%